Alternate Leg Bounding Acutely Improves Change of Direction Performance in Women's Team Sports Players Irrespective of Ground Type - Liam Kilduff (Journal of Strength and Conditioning Research, 2022)
This study aimed to assess whether post-warm-up body mass only alternate leg bounding performed on grass or a hard surface acutely improves pre-planned change of direction performance in women’s team sports players relative to a control condition and, if so, profile the time-course of such changes. On three occasions, 14 amateur women’s team sports players performed 20 m pre-planned change of direction (‘Pro-Agility’) tests at 4 min, 8 min, and 12 min following interventions. Interventions were implemented immediately after a standardized warm-up and consisted of three sets of 10 repetitions of alternate leg bounding (five ground contacts per limb) on a hard indoor surface (HARD) or natural grass (GRASS), or a control condition involving ~75 s of continuous walking with no bounding (CON). Performance was similar between conditions at 4 min post-intervention. Performance at 8 min was greater in HARD (2.9%, p = 0.015), and GRASS (3.8%, p = 0.029) relative to CON, whilst GRASS also exceeded CON at 12 min post-bounding (5.2%, p = 0.004). All effects were large. No differences existed between HARD and GRASS at any timepoint. Alternate leg bounding performed with body mass only can acutely improve indices of change of direction performance in women’s team sports players irrespective of the ground surface when an appropriate post-stimulus recovery period is provided. Bounding on grass or a hard surface represents a feasible match-day practice that enhances subsequent change of direction performance and could therefore be used as part of practically applicable pre-match, half-time, and/or pitch-side (re)warm-up activities.